2016
DOI: 10.17583/qre.2015.1473
|View full text |Cite
|
Sign up to set email alerts
|

Graduate Students’ Construction of Researcher Identities Explored Through Discourse Analysis

Abstract: While many research methods courses challenge students to make sense of their own researcher identities as they relate to research paradigms and perspectives, there is a lack of research that examines how students actually go about constructing theses identities, particularly at the level of discourse. In this study, we attended to graduate students’ talk in an introductory research methods course, taking note of how students used particular discursive resources to construct a research identity in online class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Some scholars teaching methodological and paradigmatic plurality reported pedagogical challenges such as representing multiple paradigms within time constraints and getting students to grapple with this plurality (Gunzenhauser & Gerstl-Pepin, 2006; Kuby & Christ, 2018; Roulston & Bhattacharya, 2018; Waite, 2014; Wolgemuth, 2016). A few empirical studies reflected students’ perspectives on qualitative methods training; however those relied on brief onetime reflections on a qualitative component of general research methods courses offered to master’s-level practitioner students (Cassell, 2018; Davis & Lester, 2016) or on doctoral students’ intellectual reasoning strategies when describing paradigms early on in a qualitative methods course (Schnelker, 2006). Cassell’s (2018) study of MBA students’ experiences with conducting a qualitative interview as part of a six-hour research and consultancy skill module in a research methods course showed how the course helped students learn managerial skills.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Some scholars teaching methodological and paradigmatic plurality reported pedagogical challenges such as representing multiple paradigms within time constraints and getting students to grapple with this plurality (Gunzenhauser & Gerstl-Pepin, 2006; Kuby & Christ, 2018; Roulston & Bhattacharya, 2018; Waite, 2014; Wolgemuth, 2016). A few empirical studies reflected students’ perspectives on qualitative methods training; however those relied on brief onetime reflections on a qualitative component of general research methods courses offered to master’s-level practitioner students (Cassell, 2018; Davis & Lester, 2016) or on doctoral students’ intellectual reasoning strategies when describing paradigms early on in a qualitative methods course (Schnelker, 2006). Cassell’s (2018) study of MBA students’ experiences with conducting a qualitative interview as part of a six-hour research and consultancy skill module in a research methods course showed how the course helped students learn managerial skills.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Cassell’s (2018) study of MBA students’ experiences with conducting a qualitative interview as part of a six-hour research and consultancy skill module in a research methods course showed how the course helped students learn managerial skills. Findings from the other studies (Davis & Lester, 2016; Schnelker, 2006) concentrated on three key themes: students felt unsettled by new and unfamiliar information, their arguments were rife with misconceptions, and their reasoning relied heavily on personal experiences rather than on theory.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Discourse analysis can serve as a basis for the teaching and learning of genres such as discussion sessions following conference presentations (Davies & Lester, 2016), where it is common to find an ensemble of "linguistic, visual, audio, gestural and spatial modes of meaning" (Cope & Kalantzis, 2009: 166). Although verbal expression is often considered the most significant mode of communication, multimodality shows that all modes have the potential to contribute to meaning in the same way (Jewitt, 2013).…”
Section: Introductionmentioning
confidence: 99%